Current State and Trends in the Development of E-Business in Ukraine - LAZORENKO, L.; HLUSHENKOVA, A. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2024)
The article reveals the essence of electronic business, its models and methods. The difference between the concepts of "electronic business" and "electronic commerce" is defined. E-commerce is a way of doing business, the main difference of which is sales and purchases via the Internet. This approach allows you to conduct commodity and monetary exchange without direct contact between the seller and the buyer. E-business is a way of doing business using the capabilities of the global Internet. which includes many subspecies and divisions, including e-commerce. The main e-business models are: business-to-business B2B, business-to-consumer B2C, consumer-to-consumer C2C model, consumer-to-business C2B model. The features and trends in the development of B2B and B2C models are revealed. The advantages and disadvantages of these business models are characterized. Examples of B2B and B2C business models are given. B2C models involve the purchase of goods and services by consumers solely to meet their own needs, without counting on making a profit in the future, as is the case in the B2B model. The main tools for doing business according to the B2C model have been identified, namely: e-mail marketing, SMS marketing, Web push marketing, chatbots, online chat on the site. Quite often, companies can work both in the field of B2B and B2C. Therefore, e-business is an important tool that should be used by enterprises in various aspects of the development of their activities in order to increase competitiveness in modern conditions. For this purpose, it is advisable to introduce various methods and mechanisms for the implementation and development of e-business, adopting the experience of leading companies in Ukraine and the world. It is advisable to develop marketing and product strategies, that ensure the success of e-business. But the main disadvantages of e-business should not be ignored – this is high competition, the cost of appropriate software, which will ensure not only doing business, but also the confidentiality of customer information. Enterprises should take this into account when developing their development strategy.